Slovenska podjetja in značilnosti poslovnega prestrukturiranja: Slovenski podjetniški observatorij 2020 (University of Maribor Press, 2021)
Slovenian Enterprises and the Characteristics of Business Restructuring: Slovenian Entrepreneurship Observatory 2020. In the first part of the scientific monograph, we focused on the business demography of Slovenian companies and compared it with the European one. The purpose of this chapter is to get an insight into Slovenian companies and understand how Slovenian entrepreneurship is positioned in Europe. We analysed the key characteristics of Slovenian companies and sole proprietors who were engaged in entrepreneurial activities in 2019 and were classified in all SKD activities. In Slovenia, we must encourage the establishment of new companies with growth potential and the growth of existing companies. It is also important to understand that existing companies must be constantly on the search for new opportunities and permanently adapt to changing business conditions, which is another topic of this year’s Entrepreneurship Observatory, where we are discussing business restructuring. In order to get the best possible insight into the processes of business restructuring in Slovenia, we conducted a survey among SMEs and experts in the supportive environment for entrepreneurship.